Electromagnetic ray tracing model for line structures and characterization of advanced alignment marks in photolithography - Tan, Chin Boon (2009)
Line structures are an essential part in integrated circuit (IC) fabrication. In photolithography, the electromagnetic scattering of line structures is one of the main factors that determine the advancement of the technology node. From the perspective of modeling, a theoretical model to physically understand the scattering phenomenon is necessary for a solid foundation in efficient characterization. When the domain of simulation that needs to be addressed is substantial, an approximate solution is ideal for resource efficient modeling. From the perspective of alignment using line structures, it must meet the stringent overlay budget for new fabrication processes. The robustness of the alignment marks is critical as accurate signal is required to precisely align a masking layer to the previous layer.